Transungual Penetration and Antifungal Activity of Prescription and Over-the-Counter Topical Antifungals: Ex Vivo Comparison - Ali Elabbasi; Ahmed Kadry; Warren Joseph; Boni Elewski; Mahmoud Ghannoum (Adis, Springer Healthcare, 2024)
Abstract Introduction Topical antifungals for toenail onychomycosis must penetrate the nail to deliver an inhibitory concentration of free drug to the site of infection. In two ex vivo experiments, we tested the ability of topical antifungals to inhibit growth of Trichophyton rubrum and Trichophyton mentagrophytes, the most common causative fungi in toenail onychomycosis. Methods Seven topical antifungals were tested: three U.S. Food and Drug Administration-approved products indicated for onychomycosis (ciclopirox 8% lacquer; efinaconazole 10% solution; tavaborole 5% solution) and four over-the-counter (OTC) products for fungal infections (tolnaftate 1% and/or undecylenic acid 25% solutions). The ability to inhibit fungal growth was tested in the presence and absence of keratin. Products were applied either to human cadaverous nails or keratin-free cellulose disks prior to placement on an agar plate (radius: 85 mm) seeded with a clinical isolate of T. rubrum or T. mentagrophytes. After incubation, the zone of inhibition (ZI), defined as the radius of the area of no fungal growth, was recorded. Results In the nail penetration assay, average ZIs for efinaconazole (T. rubrum: 82.1 mm; T. mentagrophytes: 63.8 mm) were significantly greater than those for tavaborole (63.5 mm; 39.1 mm), ciclopirox (7.4 mm; 3.6 mm) and all OTC products (range: 10.5-34.2 mm against both species; all P < 0.001). In the cellulose disk diffusion assay, efinaconazole and tavaborole demonstrated maximal antifungal activity against both species (ZIs = 85 mm); average ZIs against T. rubrum and T. mentagrophytes were smaller for ciclopirox (59.0 and 55.7 mm, respectively) and OTC products (range: 31.2-57.8 mm and 25.7-47.7 mm, respectively). Conclusions Among all antifungals tested, the ability to penetrate human toenails to inhibit growth of both T. rubrum and T. mentagrophytes was greatest for efinaconazole, followed by tavaborole. These results indicate superior transungual penetration of efinaconazole compared to the other antifungals, suggesting lower keratin binding in the nail.